Calf presence and milking twice daily prolongs postpartum anestrus - G.C. Lamb; L.M. Lynch; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1996)
Four treatments were initiated approximately 15 days after calving: 1) calf was weaned permanently from its dam (CW; n=6); 2) calf was present continuously with its dam (CPO; n=5); 3) calf was weaned permanently from its dam + dam was milked twice daily (CWM; n=6); 4) calf was present continuously with its dam but contact with the udder was prohibited + dam was milked twice daily (CRM; n=5). During the 4-week treatment period, cows in the CRM treatment produced about twice as much milk, milk fat, milk protein, milk lactose, and milk solids-not-fat (SNF) than CWM cows. After completion of treatments, calves were returned to their dams and allowed to suckle ad libitum. After calves had been reunited with their dams for 1 week, cows in the CRM treatment produced similar amounts of milk, milk fat, milk protein, milk lactose, and milk SNF as CPO cows, but about twice as much as CWM cows. Cows weaned and milked twice daily had their first postpartum ovulation about 2 weeks after weaning, similar to cows weaned but not milked, whereas cows milked in the presence of their own restricted calf first ovulated in about 4 weeks and calf-present cows in about 5 weeks. We conclude that both milk removal (either mechanically or by a calf) and a cow-calf bond are essential to prolong postpartum anestrus.
Keywords: Cattlemen& #x27; s Day; 1996; Kansas Agricultural Experiment Station contribution; no. 96-334-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 756; Beef; Cows; Milking; Suckling; Calf presence; Anestrus